2008
DOI: 10.1097/ico.0b013e31815c18d6
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Expression and Activation of Matrix Metalloproteinase 8 in Tear Fluid in Atopic Blepharoconjunctivitis

Abstract: : A higher mean concentration and activation of MMP-8 is present in tear fluid in ABC. This finding probably reflects persistent inflammatory and collagenolytic activity associated with the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Our study shows that the proteolytic enzyme activity is increased in NAEC: the mean MMP-8 concentration of in NAEC tears is significantly higher (3-to 4-fold higher) than for the healthy controls. We have recently demonstrated that in atopic eosinophilic blepharoconjunctivitis (ABC) patients, the MMP-8 concentration in tears was also significantly increased [24]. However, among ABC patients, the mean MMP-8 concentration was two to three times higher than among NEAC patients, which seems to separates them from the NAEC group, and further suggests that NAEC is a independent entity among chronic conjunctivitis.…”
Section: Discussionmentioning
confidence: 91%
“…Our study shows that the proteolytic enzyme activity is increased in NAEC: the mean MMP-8 concentration of in NAEC tears is significantly higher (3-to 4-fold higher) than for the healthy controls. We have recently demonstrated that in atopic eosinophilic blepharoconjunctivitis (ABC) patients, the MMP-8 concentration in tears was also significantly increased [24]. However, among ABC patients, the mean MMP-8 concentration was two to three times higher than among NEAC patients, which seems to separates them from the NAEC group, and further suggests that NAEC is a independent entity among chronic conjunctivitis.…”
Section: Discussionmentioning
confidence: 91%
“…Studies on the cornea in vitro and in vivo have underscored the role of MMPs in normal and pathological epithelial wound healing, stromal remodeling and corneal ulceration 9,10 . Furthermore, studies of human tears showed elevated levels and activities of MMPs in inflammatory ocular surface diseases such as dry eye 11 , infective keratitis 12 , active peripheral ulcerative keratitis 13 , atopic blepharoconjunctivitis 14 , ocular rosacea 15 , vernal conjunctivitis 16 and non-allergic eosinophilic conjunctivitis 17 . Inflammatory cells, particularly neutrophils, are major sources of neutrophil collagenase (MMP-8) and gelatinase B (MMP-9), both of which have been associated with the extent of cellular inflammation 12,14,18,19 .…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, MMP-2 and MMP-9 are gelatinases that degrade type IV collagen, the major structural component of the ECM [4]. These proteases were found to take part in many ocular disorders like retinopathy [5], cataract [6], uveitis [7], or generally atopic ocular diseases [8]. In turn, local micromolar NO concentrations may exert similar effects that are connected with inflammation and local tissue destruction.…”
Section: Introductionmentioning
confidence: 99%